1997
DOI: 10.1002/(sici)1099-1166(199706)12:6<599::aid-gps505>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Quality of Life in Elderly People Using Psychological Testing

Abstract: To study factors which influence the quality of life (QOL) in the elderly, we investigated the relationship between scores on the modified Philadelphia Geriatric Center (JPGC) Morale Scale and various other psychological tests in 51 elderly people residing in a long‐term care facility. The JPGC Morale Scale score correlated with the scores for all sections of the Japanese version of the Cornell Medical Index (JCMI), but not with those for the Mini Mental State Examination, the Kohs block design test, the Bende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 11 publications
3
12
1
Order By: Relevance
“…The overall mean PGC morale scale score in the above three reports was 13.5 ( n = 464), being slightly higher than the results of this study. The mean score on the revised PGC morale scale was comparable to the score of 10.0 observed among the Japanese elderly living in a special nursing home, 6 but it was lower than the scores observed among community-dwelling elderly in other reports (in Maeda et al ., 5 Yasunaga et al ., 7 Nagata et al . 8 and Fukuda et al .…”
supporting
confidence: 41%
“…The overall mean PGC morale scale score in the above three reports was 13.5 ( n = 464), being slightly higher than the results of this study. The mean score on the revised PGC morale scale was comparable to the score of 10.0 observed among the Japanese elderly living in a special nursing home, 6 but it was lower than the scores observed among community-dwelling elderly in other reports (in Maeda et al ., 5 Yasunaga et al ., 7 Nagata et al . 8 and Fukuda et al .…”
supporting
confidence: 41%
“…Meanwhile, Nagatomo et al (1997) averred that ADL is not associated with morale. Onishi et al (2005), for their part, stated that higher morale is significantly correlated with independence in ADL.…”
Section: Functional Abilitymentioning
confidence: 99%
“…Currently, the literature on the well-being of elderly people across cultures (Wong, Woo, Hui, & Ho, 2004) has been given considerable attention. Well-being of elderly people has been studied in Umeå (von HeidekenWagert et al, 2005); Japan (Kudo et al, 2007;Nagatomo, Kita, Takigawa, Nomaguchi & Sameshima, 1997); Turkey (Pinar & Oz, 2011); and Hong Kong (Wong et al, 2004;Woo, Ho, & Wong, 2005). However, the well-being of elderly people in the Philippines has not been investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Norwegian study found a 31% prevalence of depression among recently admitted long-term care patients (Iden et al, 2014). NPS affect patients' quality of life (QoL) (Beerens et al, 2013;Mjørud et al, 2014b), and low QoL is associated with impaired mobility, lack of social activities and low performance in activities relating to daily living (Nagatomo et al, 1997;Barca et al, 2011;Telenius et al, 2013;Mjørud et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%